(untitled) (International Journal of Nursing Education, 2023)
Mental health challenges can develop during the prenatal and postpartum periods when women face physical,mental, and social adjustments. The major public health concern is postpartum depression, which poses aserious threat to mothering and has serious consequences for families. The number of women who experiencedepression during pregnancy or within the first 12 months after giving birth ranges from 10 to 20 percent.The clinics primarily use questionnaires to diagnose patients. Treatment options include psychotherapy andantidepressant medications. Postpartum depression and the factors associated with postpartum depressionamong women of childbearing age are the focus of this review.